1981
DOI: 10.2307/3280565
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Action Enhanced by Photoaffinity Labeling with Ethidium Analogs

Abstract: The trypanocidal activity of photoreactive azido analogs of ethidium was tested to determine the suitability of using such compounds as in vivo probes to study the mechanism of the antitrypanosomal activity of ethidium. Eight ethidium analogs, including three nonphotoreactive compounds, were tested for their ability to kill T. brucei both with and without photolytic activation. Two analogs tested, the monoamino-monoazido isomers, showed greater that 100-fold enhancement of trypanocidal activity following photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Ethidium monoazide (8-azido-3-amino-5-ethyl-6phenylphenanthridium-chloride) seems to be an appropriate wotoaffinity label of ethidium bromide since the equilibrium interactions and biological properties of the photoreactive derivative are very similar to the parent compound (Hixon etal., 1975;Garland et al, 1980;Fukunaga etal. , 1980;Graves et al, 1981;Laugaa et a/., 1983;Cox et a / . .…”
Section: Introductionmentioning
confidence: 99%
“…Ethidium monoazide (8-azido-3-amino-5-ethyl-6phenylphenanthridium-chloride) seems to be an appropriate wotoaffinity label of ethidium bromide since the equilibrium interactions and biological properties of the photoreactive derivative are very similar to the parent compound (Hixon etal., 1975;Garland et al, 1980;Fukunaga etal. , 1980;Graves et al, 1981;Laugaa et a/., 1983;Cox et a / . .…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the nitrene also reacts with the deoxyribose, and the reaction with the sugar causes chain breakage. Cox et al (6) reported anti-trypanosomal activity of EMA, and Rueckert et al (27) reported the bactericidal effect of EMA on Anoxybacillus flavithermus. However, the mechanism had not been extensively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of OC band was strongest at the concentration of 50 ng/ml of EMA, and OC bands became weaker again at 75 and 100 ng/ml of EMA compared with that of 50 ng/ml of EMA (lanes 7-9). This result shows that a single-stranded breakage occurred at the range of 10 to 100 ng/ml of EMA, and the shape of DNA changed from SC to OC (lanes [3][4][5][6][7][8][9]. At the range of 500 ng/ml to 10 µg/ml, both of SC and OC bands of pBR322 DNA disappeared, which shows that cleavage of double- stranded DNA took place (lanes 10-13).…”
Section: Effect Of Concentrations Of Ema On the Cleavage Of Negativelmentioning
confidence: 94%
See 1 more Smart Citation
“…36 The monoazido analogs of ethidium have been established as appropriate probes for understanding ethidium-DNA interactions. The noncovalent DNA-binding properties of the monoazido analogs were found previously to mimic those of the parent ethidium compound when they were examined and compared by uv-visible and fluorescence spectroscopic m e t h o d~.~O %~~J~…”
Section: Ethidium As a Probementioning
confidence: 99%